MENINGKATKAN KEMAMPUAN GURU DALAM PENGUATAN PENDIDIKAN KARAKTER SISWA ASPEK PEDULI LINGKUNGAN MELALUI PEMBINAAN UKS: DOI: https://doi.org/10.37850/cendekia.v12i1.115. - Ngatini, Ngatini (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2020)
Based on the assessment of the ability of teachers in strengthening the character education of students concerned about the environment in pre-cycle it can be seen that the ability of teachers in strengthening the character education of students caring about the environment in the low category because it only gets an average score of 1.06. Furthermore, based on the assessment of the ability of teachers in strengthening the character education of students concerned about the environment in the first cycle it can be seen that the ability of teachers in strengthening the character education of students caring about the environment in the category of teacher ability in strengthening the character education of students caring about the environment is due to getting an average score of 3, 12 Evidently there is an increase in the ability of teachers in strengthening the character education of environmental aspects of students seen from the average assessment of the ability of teachers in strengthening the character education of environmental aspects of students initially in the pre-cycle conditions showed a low average rating of 1.06 increased to the ability category the teacher in strengthening the character education of students concerned about the environment because of getting an average score of 3.12. Even so the improvement of the ability of teachers in strengthening the character education of students concerned about the environment after the implementation of UKS in the first cycle has not been able to reach the target set, namely 100% of teachers have an assessment of the ability of teachers in strengthening character education of students who care about the environment. For this reason, the implementation of the first cycle needs to be evaluated and reflected. Based on the assessment of the ability of teachers in strengthening the character education of students concerned about the environment in the second cycle can be seen that the average score indicates a value of 4.5 or included in the high category. It can be seen that the ability of teachers in strengthening the character education of environmental aspects of students in SKH Negeri 01 Tangerang Regency is already high.